Synthesis and Antimicrobial Activities of 1-(Substituted pyrimidino)-substituted thiocarbamides - TAYADE, D.T.; WAGHMARE, J.S.; PATIL, S.U. (Asian Journal of Chemistry, 2010)
1-(4-Hydroxy-6-methyl-pyrimidino)-3-substituted thiocarbamides (7a-f) and 1-( 4-hydroxy-5-benzyl-6-methyl pyrimidino)-3-substituted thiocarbamides (8a-f) have been successfully synthesized by condensing 2-amino-4-hydroxy-6-methyl pyrimidine (4) and 2-amino-4-hydroxy-5-benzyl-6-methylpyrimidine (5) with various isothiocyanates (6a-f) in acetone medium. Compounds (4) and (5) were obtained by reinvestigating the interaction of guanidine (1) with acetoacetic ester (2) and ethyl-α-benzyl-β-keto butyrates (3) respectively. Antimicrobial activities of these newly synthesized compounds were carried out by MIC method.